2010
DOI: 10.1371/journal.pbio.1000382
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Assignment and Maintenance of Positional Identity in the Ventral Neural Tube by the Morphogen Sonic Hedgehog

Abstract: During development of the vertebrate neural tube, cells acquire their positional identity from not only the spatial level of the Sonic Hedgehog signaling gradient, but also the temporal duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
235
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(263 citation statements)
references
References 84 publications
(134 reference statements)
27
235
1
Order By: Relevance
“…These data also suggest that this remaining expression of pMN, p2 and p1 genes is sufficient to specify the postmitotic cells that we observe in the zebrafish ventral spinal cord in the absence of Hh signalling. Our results are consistent with data from Dessaud and colleagues (Dessaud et al, 2010) that suggest that in amniotes the duration of Shh signalling is as important as the levels of signalling for specifying distinct ventral spinal cord fates, although our data suggest that it is continued inhibition of Gli repressor activity (see below) that is important, rather than Hh signalling per se. Taken together, the simplest model for reconciling these different mouse and zebrafish phenotypes is that, in zebrafish, Gli repressor activity is not present in the ventral spinal cord until the early to mid-somitogenesis stages and that this is too late to repress the initial expression of p2 and p1 domain transcription factors and the formation of V2 and V1 cells, although it is sufficient to repress p2 and p1 domain expression at later stages.…”
Section: Research Articlesupporting
confidence: 92%
“…These data also suggest that this remaining expression of pMN, p2 and p1 genes is sufficient to specify the postmitotic cells that we observe in the zebrafish ventral spinal cord in the absence of Hh signalling. Our results are consistent with data from Dessaud and colleagues (Dessaud et al, 2010) that suggest that in amniotes the duration of Shh signalling is as important as the levels of signalling for specifying distinct ventral spinal cord fates, although our data suggest that it is continued inhibition of Gli repressor activity (see below) that is important, rather than Hh signalling per se. Taken together, the simplest model for reconciling these different mouse and zebrafish phenotypes is that, in zebrafish, Gli repressor activity is not present in the ventral spinal cord until the early to mid-somitogenesis stages and that this is too late to repress the initial expression of p2 and p1 domain transcription factors and the formation of V2 and V1 cells, although it is sufficient to repress p2 and p1 domain expression at later stages.…”
Section: Research Articlesupporting
confidence: 92%
“…Experimental work in Drosophila and in vertebrates indicates that the Hh signaling pathway is subject to extensive feedback among elements of the pathway, most notably that of the Hh receptor patched (ptc) (Chen and Struhl, 1996;Marigo and Tabin, 1996). Furthermore, the combination of experimental and modeling studies on developing fly wings and on vertebrate neural tube and limbs have uncovered new roles for this feedback in the dynamics of Hh gradient formation, in its robustness and in the generation of distinct patterns of target gene expression (Briscoe et al, 2001;Saha and Schaffer, 2006;Dessaud et al, 2007;Dessaud et al, 2008;González et al, 2008;Nahmad and Stathopoulos, 2009;Dessaud et al, 2010;Irons et al, 2010;Probst et al, 2011;Balaskas et al, 2012). Therefore, the iteration between mathematical modeling and experimentation is emerging as a productive way of illuminating the problem of Hh morphogen action during organ growth and patterning.…”
Section: Introductionmentioning
confidence: 99%
“…Recent fate-mapping studies based on the Cre-loxP strategy indicated that the Nkx2-2 and Olig2 cell lineages may share a common origin (Wu et al, 2006;Dessaud et al, 2007Dessaud et al, , 2010Holz et al, 2010;Chen et al, 2011;Wang et al, 2011), a result that is supported by the analysis of the temporal expression profile of several transcription factors (Jeong and McMahon, 2005;Lek et al, 2010). It is therefore important to understand how the Olig2/Nkx2-2 double-positive (Olig2 + /Nkx2-2 + ) cells diversify into Olig2 + pMN progenitors and Nkx2-2 + p3 progenitors.…”
Section: Introductionmentioning
confidence: 99%